Еколого - гігієнічні аспекти антропогенного забруднення води поверхневих водойм Українського Придунав’я = Ecologic – and - hygienic aspects of anthropogenic pollution of surface water bodies in Ukrainian Danube region - Kovalchuk, L. I.; Korobchansky, V. A.; Mokienko, A. V. (Journal of Education, Health and Sport, 2015)
Kovalchuk L I., Korobchansky V. A., Mokienko A. V. Еколого - гігієнічні аспекти антропогенного забруднення води поверхневих водойм Українського Придунав’я = Ecologic – and - hygienic aspects of anthropogenic pollution of surface water bodies in Ukrainian Danube region. Journal of Education, Health and Sport. 2015;5(8):137-144. ISSN 2391-8306. DOI 10.5281/zenodo.27739 http://dx.doi.org/10.5281/zenodo.27739 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A137-144 https://pbn.nauka.gov.pl/works/606472 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. УДК 615.327.036.8:613.3 (477.53) еколого - Гігієнічні аспекти антропогенного забруднення ВОДИ поверхневих водойм Українського Придунав’я Ecologic – and - hygienic aspects of anthropogenic pollution of surface water bodies in Ukrainian Danube Region * Л. Й. Ковальчук, ** В. О. Коробчанський, *** А. В. Мокієнко * L I. Kovalchuk, ** V. A. Korobchansky, *** A. V. Mokienko *Одеський національний медичний університет; **Харківський національний медичний університет; *** Державне підприємство Український науково-дослідний інститут медицини транспорту Міністерства охорони здоров’я України, м. Одеса *Odessa National Medical University; **Kharkiv National Medical University; ***State Enterprise Ukrainian Research Institute for Medicine of Transport of the Ministry of Health Care of Ukraine, Odessa Abstract The objective: to analyze the ecological – and - hygienic aspects of anthropogenic pollution of surface water reservoirs in Ukrainian Danube region. It has been established that the content of inorganic nitrogen compounds of biogenic origin, the waters under study may be referred to the sources of 2nd -4th class. It may indicate presence of organic anthropogenic pollution sources. According to the content of phenols and oil the water of lakes and small rivers refers to class 2. High levels of surface water pollution with general organic carbon, which is unfavourable prognostic factor of hazardous halogenated organic compounds formation in chlorination of water has been deternmined. Definite levels of water pollution of lakes and small rivers with heavy metals - cadmium, manganese, copper, vanadium haave been established. The presence drinking water intakes contamination with CVD (DDT, lindane) and PCBs, as well as man-made origin of PAHs have been revealed. The necessity of systematic monitoring of surface waters of Ukrainian Danube region has been substantiated. It should be accompanied by identification and possible elimination of pollution sources. Keywords: water, water bodies, anthropogenic pollution, Ukrainian Danube region. Реферат Мета роботи полягала в аналізі еколого-гігієнічних аспектів антропогенного забруднення води поверхневих водойм Українського Придунав’я. Встановлено, що за вмістом неорганічних сполук азоту, які мають біогенне походження, вивчені водні об’єкти відносяться до джерел 2-4 класу, що може свідчити про наявність джерел органічного антропогенного забруднення. За вмістом фенолів та нафтопродуктів вода озер та малих річок відповідає 2 класу. Констатовано високі рівні забруднення води поверхневих водойм загальним органічним вуглецем, що є прогностично несприятливим фактором утворення при хлоруванні води небезпечних для здоров’я галогенорганічних сполук. Встановлено певні рівні забруднення води озер та малих річок важкими металами (кадмій, марганець, мідь, ванадій). Показано наявність забруднення води питних водозаборів ХОП (ДДТ, лінданом) та ПХБ, а також техногенність походження ПАВ. Обгрунтовано необхідність систематичного моніторингу стану поверхневих водойм Українського Придунав’я, що доцільно супроводжувати ідентифікацією та можливим вилученням джерел забруднення. Ключові слова: вода, водні об’єкти, антропогенне забруднення, Українське Придунав’я. Реферат Эколого - ГИГИЕНИЧеские аспекты АНТРОПОГЕННОГО ЗАГРЯЗНЕНИЯ ВОДЫ ПОВЕРХНОСТНЫХ ВОДОЕМОВ УКРАИНСКОГО ПридунавЬя. Цель работы состояла в анализе эколого – гигиенических аспектов антропогенного загрязнения воды поверхностных водоемов Украинского Придунавья. Установлено, что по содержанию неорганических соединений азота, которые имеют биогенное происхождение, изученные водные объекты относятся к источникам 2-4 класса, что может свидетельствовать о наличии источников органического антропогенного загрязнения. По содержанию фенолов и нефтепродуктов вода озер и малых рек отвечает 2 классу. Констатированы высокие уровни загрязнения воды поверхностных водоемов общим органическим углеродом, что является прогностически неблагоприятным фактором образования при хлорировании воды опасных для здоровья галогенорганических соединений. Установлены определенные уровни загрязнения воды озер и малых рек тяжелыми металлами - кадмием, марганцем, медью, ванадием. Показаны наличие загрязнения воды питьевых водозаборов ХОП (ДДТ, линданом) и ПХБ, а также техногенность происхождения ПАУ. Обоснована необходимость систематического мониторинга состояния поверхностных водоемов Украинского Придунавья, что целесообразно сопровождать идентификацией и возможным устранением источников загрязнения. Ключевые слова: вода, водные объекты, антропогенное загрязнение, Украинское Придунавье.